Pola Komunikasi Keluarga dalam Menghadapi Sibling Rivalry Prespektif Dr.Aisyah CH.t - Luthfi Hidayah, Luthfi Hidayah; Rohmatillah, Iga Nur; Selvia Assoburu; Khoridatun Nafisah, Luthfi Hidayah (Conseils : Jurnal Bimbingan dan Konseling Islam, 2025)
Family communication patterns play an important role in building closeness to children in order to create a harmonious relationship. Interaction and communication in the family are not only carried out with parents, but also with siblings, both older and younger. In order to create harmony between the two, parents should not compare in order to avoid quarrels between siblings (Sibling Rivalry). Researchers use qualitative research methods. Data collection techniques used include interviews, observations and documentation, then a conclusion can be drawn. In analyzing research problems, researchers focus on using the theory of family communication patterns (Family Communication Pattern Theory). Researchers can conclude that the family communication pattern used is a pluralistic family communication pattern, where the family has a high conversation orientation and a low conformity orientation so that it is open without limitations. Parents are open to the values ​​and beliefs in the family. However, parents can also accept differences of opinion from children.